1994
DOI: 10.2337/diab.43.11.1345
|View full text |Cite
|
Sign up to set email alerts
|

Intraportal Transplantation of Pancreatic Islets Into Livers of Diabetic Rats: Reinnervation of Islets and Regulation of Insulin Secretion by the Hepatic Sympathetic Nerves

Abstract: Two weeks after intraportal transplantation of 2,000 neonatal pancreatic islets, recipient rats completely recovered from streptozotocin-induced diabetes. The reversal of diabetes could be documented by the normalization of blood glucose levels, by a restored weight gain, by normal glucagon and insulin levels in blood, and by a disappearance of polyuria and polydipsia. The reversal remained stable for at least 9 months. This study determined whether intraportally transplanted pancreatic islets were reinnervate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The endocrine function of retrieved intraportally transplanted islets seemed even more impaired than expected based on previous results from perfusion of graft-bearing livers in rat (12,22,23). We have previously thoroughly evaluated our technique to retrieve intraportally transplanted islets and found that the procedure in itself is unlikely to damage the islet cells (5).…”
Section: Discussionmentioning
confidence: 88%
“…The endocrine function of retrieved intraportally transplanted islets seemed even more impaired than expected based on previous results from perfusion of graft-bearing livers in rat (12,22,23). We have previously thoroughly evaluated our technique to retrieve intraportally transplanted islets and found that the procedure in itself is unlikely to damage the islet cells (5).…”
Section: Discussionmentioning
confidence: 88%
“…Both parasympathetic and sympathetic innervations contribute in a redundant fashion to ␣-cell activation during hypoglycemia (13,34). The absent pancreatic polypeptide response to hypoglycemia demonstrated here suggests a lack of parasympathetic innervation, although sympathetic innervation of intrahepatic islets might occur along vascular channels (35). Although innervation does not appear necessary for an intact ␣-cell response to hypoglycemia after transplantation of a denervated whole pancreas (36 -38), neural activation may be more important when the mass of cells is reduced as after islet transplantation.…”
Section: Fig 3 Plasma Glucose (A) and Incremental Glucagon (B) Durimentioning
confidence: 81%
“…43,44 Correlation was shown between the success rate for diabetes reversal and the minimal number of syngeneic islets: 100% reversal with 1000 islets (approximately 3500 islets/ kg), 33% with 700 islets (2500 islets/kg), and 0% with 500 islets (1700 islets/kg). In the 1990s, 2000 syngeneic islets were reported to reverse diabetes in LEW rats.…”
Section: Comparison To Previous Rat Intrahepatic Transplantationsmentioning
confidence: 98%